Analisis Kemampuan Pemahaman Konsep Matematika Pada Materi Perkalian Siswa Kelas IV SD - Sagita Ratiana; Alani, Nabella; Tryana, Diena; Cikal, Aulia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the low and uneven distribution of elementary students’ mathematical conceptual understanding, particularly in multiplication, which is often learned procedurally without deep conceptual meaning. This study aims to analyze the level of students’ mathematical conceptual understanding in multiplication among fourth-grade elementary school students. The research employed a quantitative descriptive approach involving 20 students of SDN 3 Sukahaji. Data were collected through a mathematical conceptual understanding test developed based on key conceptual understanding indicators, while data analysis was conducted using descriptive statistics, including mean, median, mode, as well as the highest and lowest scores. The results revealed that the average student score was 77, which falls into the medium category, with the highest score of 92 and the lowest score of 60, indicating variability in students’ abilities. Based on the categorization results, most students were classified into the medium category, followed by high and low categories, suggesting that students’ conceptual understanding is not yet evenly distributed. These findings imply the need for improvements in the learning process through the implementation of student-centered learning strategies and the use of contextual and varied instructional media to enhance students’ conceptual understanding more effectively